IDENTIFIKASI INTELINGENSI ANAK NELAYAN/PELAKU UTAMA/ JALUR KHUSUS DI POLITEKNIK KELAUTAN DAN PERIKANAN BITUNG - Adi Suseno; Asia Asia; Daniel H. Ndahawali; Dolfie Dj Kaligis; Heru Santoso; Palehel Mulalinda; Jerry D. Kalesaran; Itje Wewengkang; Peggy Pontoh (Politeknik Kelautan dan Perikanan Bitung, 2019)
Bitung Marine and Fisheries Polytechnic is located in the city of Bitung, North Sulawesi province. One of the universities under the Maritime and Fisheries Polytechnic under the Ministry of Maritime Affairs and Fisheries, Bitung, is a vocational university in Indonesia in the field of Marine and Fisheries in 2015, starting to recruit fishermen / main actors / special pathways. The time of the study was conducted in August 2018 until November 2018. Locations at the Bitung Marine and Fisheries Polytechnic. Sources of data obtained from students at the Polytechnic KP Bitung special lane (children of the main actors / fishermen). Furthermore, scoring and analysis using Cattel 1971 analysis. The conclusions in this study are the conditions of level I, II and III of the main actors. Midshipman and junior high school level 51.9 percent in the average category. Midshipmen and junior high school level II are 60 percent average. Midshipman-leveluni level III 55.3 percent in the average category.